To multiply the polynomials \((6x + 2)(4x - 3)\), we can use the distributive property (also known as the FOIL method for binomials):
\[ (6x + 2)(4x - 3) = 6x(4x) + 6x(-3) + 2(4x) + 2(-3) \]
Now we calculate each term:
- \(6x \cdot 4x = 24x^2\)
- \(6x \cdot (-3) = -18x\)
- \(2 \cdot 4x = 8x\)
- \(2 \cdot (-3) = -6\)
Now, we combine these results:
\[ 24x^2 - 18x + 8x - 6 \]
Next, we combine the like terms \(-18x\) and \(8x\):
\[ 24x^2 + (-18x + 8x) - 6 = 24x^2 - 10x - 6 \]
Thus, the product \((6x + 2)(4x - 3)\) expressed as a polynomial in standard form is:
\[ \boxed{24x^2 - 10x - 6} \]